Effects of salt concentration on vapor-liquid equilibrium (VLE) of azeotropic mixture in ultrasonic distillation system - Razali, Nor Faizah (2008)
Methanol and methyl acetate form an azeotrope in their mixtures at 34.78 mole % of methanol. It is difficult and may be impossible to separate azeotropic mixture using conventional distillation column. This phenomenon gives big challenges in the chemical industry in order to solve it. In this study, potassium chloride was added in ultrasonic distillation system to study the combination effect of salt and ultrasonic wave on methanol-methyl acetate mixture. The salt was added with different range of concentration to select the optimum concentration that can eliminate the azeotropic point. Ultrasonic wave with frequency of 25 kHz and intensity of 200 W/A.cm were used. The studies on the effect of different salt concentration at 0 wt%, 5 wt%, 10 wt% and 15 wt% to VLE of binary mixtures were done at that frequency and intensity to obtain the best salt concentration. The results obtained show that, as the salt concentration increased in the liquid phase, the equilibrium line shifts upwards and in the same time, the azeotropic point also move upward. The salt concentration used in this work give the results in the following order 15 wt% >10 wt% > 5 wt% > 0 wt% where the azeotropes point form at 70 mole %, 54 mole %, 48 mole % and 38 mole % of methanol accordingly. As the result, the best concentration of the potassium chloride for the methanol-methyl acetate separation in this project was at 15 wt% of concentration. These results show that the combination of ultrasonic and salt as a separating agent gave positive results and have a potential to be apply for industry in the future.